PENGARUH KOMPETENSI, PENGALAMAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ( - Wahyu Fitriani Gunawan; Nurwati Nurwati; Nasrul Nasrul (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
This study aims to examine and explain how much influence Competence, Work Experience and work environment has on the performance of civil servants at the Regional Inspectorate Office in North Konawe district. The design of this research uses an explanatory research approach with data collection carried out in a cross-section through a questionnaire. The sample used in this study amounted to 39 respondents who were civil servants of the North Konawe District Inspectorate. The parametric tool used to answer the hypothesis in this study uses multiple linear regression through the SPSS version 20.0 program. The results of the study show that competence, work experience and work environment simultaneously have a positive and significant effect on employee performance.The results of the study also showed that Competence partially had a positive and significant effect on employee performance, Work Experience partially had a positive and significant effect on employee performance and the Work Environment partially had a positive and significant effect on the performance of the Regional Inspectorate staff of Konawe Utara Regency.Keywords: competence, work experience, work environment, employee performance